Architectural Change as a Socio-Ecological Transition in Lo Manthang - Inu Shakya,; Singh, Bijay (Advances in Engineering and Technology: An International Journal, 2026)
Vernacular architecture in extreme environments embodies a long- term adaptation to ecological constraints, material scarcity and socio-cultural governance. Its traditional building practices, characterised by thick earthen walls, compact settlement morphology, integrated livestock stables, dry sanitation systems, courtyards and small openings, represent long-standing adaptive responses to harsh climate, limited biomass and agro-pastoral livelihoods. Drawing on the Socio-Ecological System (SES) framework, this article conceptualises architecture as a mediating mechanism between climate, resource use and cultural practices, rather than a material entity. Using qualitative case study methods including architectural documentation, field observations, and semi-structured interviews, this article traces recent architectural transitions, driven by infrastructural connectivity, tourism-oriented economies and changing social lifestyles. The recent shift towards using imported materials and construction technologies, such as cement, CGI roofing, septic tanks and altered spatial organisation signals a growing detachment of architecture from local ecological limits. Findings indicate that while contemporary materials improve hygiene, comfort and economic opportunities linked to tourism, they also disrupt local material ecologies, circular nutrient cycles, and thermal symbiosis between human and livestock, increasing reliance on external resources. The article discusses that the SES lens enables a more nuanced interpretation of architectural change beyond the traditional and modern debate. It concludes that recognising vernacular architecture as a socio-ecological process yields context-sensitive adaptation in the fragile Himalayan landscape.